2015
DOI: 10.1596/978-1-4648-0417-5
|View full text |Cite
|
Sign up to set email alerts
|

Educating the Next Generation: Improving Teacher Quality in Cambodia

Abstract: This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judgment on the part of The World Bank concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Recent generations of youth enjoy greater access to schooling than previous ones; 49 percent of youth finish their education at a level higher than their father and 63 percent finish at a level higher than their mother (ILO, 2013). Net primary enrollments increased from 84 percent in 1992 to 96.4 percent in 2012, and net secondary enrollments from 16.6 percent in 2000 to 35 percent in 2012 (Tandon and Fukao, 2015). The labor market in Cambodia also went through a transformation in part due tostrong economic growth for the last two dacades: salaried employment rose one-third in this period from 23 percent in 2004 to 30 percent in 2011 (ILO, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent generations of youth enjoy greater access to schooling than previous ones; 49 percent of youth finish their education at a level higher than their father and 63 percent finish at a level higher than their mother (ILO, 2013). Net primary enrollments increased from 84 percent in 1992 to 96.4 percent in 2012, and net secondary enrollments from 16.6 percent in 2000 to 35 percent in 2012 (Tandon and Fukao, 2015). The labor market in Cambodia also went through a transformation in part due tostrong economic growth for the last two dacades: salaried employment rose one-third in this period from 23 percent in 2004 to 30 percent in 2011 (ILO, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the difference between a high and low quality teacher amounts to a difference of 0.36 standard deviations (SDs) in student test scores in Uganda (Buhl-Wiggers et al 2017), and a 0.54 SD difference in Pakistan (Bau and Das 2017). Unfortunately, researchers have found that a large proportion of teachers in developing countries are ill-prepared for teaching, lacking the requisite knowledge and skills to improve student achievement (Behrman et al 1997;Villegas-Reimers 1998;Ball 2000;Behrman, Ross, and Sabot 2008;Bruns and Luque 2015;Tandon and Fukao 2015;Bold et al 2017). Despite sometimes high levels of formal education among teachers, many exhibit weak cognitive skills and ineffective classroom practice (Bruns and Luque 2015;Bold et al 2017).…”
mentioning
confidence: 99%
“…Benveniste et al (2008) report that the majority of class time is used for instruction or recitation with little time for group work and applied individual work. Similarly, Tandon and Fukao (2015) report that for most of the lesson teachers are dictating or students are copying off the board and there is little opportunity for feedback or applied activities. Tandon and Fukao (2015) also examine pedagogical approaches exhibited by the teacher trainers in the country's 10 Teacher Training Colleges and conclude that teacher training is also highly teacher-centered with little interaction.…”
Section: Cambodiamentioning
confidence: 99%